Evaluation of Pigeon Pea Lines for Biological Soil Decompaction - Rodolfo Godoy; Osny Oliveira Santos Bacchi; Fernando Almeida Moreira; Klaus Reichardt (International Journal of Agronomy)
Soil decompaction is generally achieved through mechanical cultivation practices; however biological processes can significantly add to this process through root growth, development, and later senescence. This study was carried out in Piracicaba, SP, Brazil and had the purpose of selecting, among forty one pure pigeon pea lines, the most efficient genotypes that promote soil decompaction by roots penetrating compacted soil layers. Utilizing artificially compacted 30 mm high soil blocks, in a series of experiments, these lines were compared to the cultivar Fava Larga taken as a standard. Three lines were preliminarily selected out of the initial group, and afterwards, in more detailed screenings by monitoring soil resistance to penetration and also evaluating the behavior of Tanzania grass plants seeded after pigeon pea, two of them, g5-94 and g8-95, were selected as possessing the most fit root system to penetrate compacted soil layers.